Menjaga Keamanan Digital Strategi serta Kebijakan Swiss dalam Mengatasi Ancaman Ransomware - Farisin, Mokhamad Saiful (Interdependence Journal of International Studies, 2025)
The global rise in cybersecurity threats has also impacted Europe, with Switzerland experiencing ransomware attacks across diverse sectors, including private companies and banking institutions. This study aims to examine Switzerland's strategies and policies in response to these challenges. Using a descriptive methodology, data was gathered through a literature review. The findings reveal that Switzerland has implemented two primary strategies to address ransomware issues: the National Cybersecurity Strategy (NCS) and the National Cyber Security Centre (NCSC). In conclusion, the author proposes policy recommendations, such as enacting more comprehensive regulations and enhancing employee awareness within companies, to bolster Switzerland's defense against ransomware and improve preparedness and risk mitigation in the face of evolving cyber threats.